2011
DOI: 10.1080/10440046.2011.579832
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Intensification, Monocultures, and Economic Failure: The Case of Onion Production in the Tipajara Watershed on the Eastern Slope of the Bolivian Andes

Abstract: This article documents and analyzes the historical process of agricultural intensification in Bolivia's Tipajara watershed. There is a particular focus on the recent rise and decline of a commercial onion monoculture. An econometric model indicates altered livelihood patterns as an outcome of the combination of rising costs for pesticides and declining yields from disease. Reliance on pesticides and a failure to rotate crops has led to an increase in the incidence of disease-causing organisms, which has result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Higher input use might also encourage diversification practices, such as integrated fish and rice farming 63 , integrated rice and fruit production (such as mango) 55 and vegetable diversification 54,64 . Our set of cases also shows that studies that find lose-lose outcomes often point to a shortage of inputs as a determining factor 40,41,[49][50][51]65 . These cases show that various types of intensification increase the need for further inputs and that these are either not available or, more often, not affordable.…”
Section: Literature Synthesismentioning
confidence: 68%
See 2 more Smart Citations
“…Higher input use might also encourage diversification practices, such as integrated fish and rice farming 63 , integrated rice and fruit production (such as mango) 55 and vegetable diversification 54,64 . Our set of cases also shows that studies that find lose-lose outcomes often point to a shortage of inputs as a determining factor 40,41,[49][50][51]65 . These cases show that various types of intensification increase the need for further inputs and that these are either not available or, more often, not affordable.…”
Section: Literature Synthesismentioning
confidence: 68%
“…3e). Nine of the 11 'lose-lose' cases report dual losses for biodiversity and well-being and four of the lose-lose cases report dual losses for biodiversity and food security [38][39][40][41] . Outcomes combining aggregate well-being gains with aggregate ecosystem service loss (win-lose) are the most likely type of outcome to occur (23% of cases).…”
Section: Literature Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Religious or cultural rituals in agrarian communities can also be designed to enhance crop yields by supporting beneficial animal interactions, particularly biological control (e.g., Ulluwishewa 1992). In cases where complex social-ecological farming systems are replaced with intensive, high-input production models, this can create a negative feedback effect on production, whereby increased pest and disease activity associated with monoculture farming exacerbate social costs, thus increasing farm abandonment and collapse of the social structure supporting the agroecosystem (Altieri 2004;Aragona and Orr 2011).…”
Section: Activity Of a Single Animal Species Can Have Different Effecmentioning
confidence: 99%
“…At small scales, variation in vegetation structure and resource availability can influence population dynamics and distribution patterns of invertebrates, including ecosystem service providers such as pollinators (Williams & Kremen, ; Murray et al , ) and natural enemies (Landis et al , ; Gámez‐Virués et al , ). Pollination and pest control services are vital for minimizing ‘yield gaps’ in agricultural production (Bommarco et al , ; Lundin et al , ; Classen et al , ) and previous studies have shown that conversion of heterogeneous landscapes to monoculture crop systems is linked to increased pests and diseases, as well as subsequent declines in crop yield (Marshall & Foot, ; Altieri & Nicholls, ; Aragona & Orr, ; Bennett et al , ). Wild pollinators can be particularly vulnerable to the intensive management of farmland that creates structural and biotic homogeneity because these insects require access to heterogeneous resources throughout the year (Williams & Kremen, ; Winfree et al , ).…”
Section: Introductionmentioning
confidence: 99%